Biofilm morphology and antibiotic susceptibility of methicillin-resistant Staphylococcus aureus (MRSA) on poly-D,L-lactide-co-poly(ethylene glycol) (PDLLA-PEG) coated titanium - Adam Benedict Turner; David Zermeño-Pérez; Margaritha M. Mysior; Paula Milena Giraldo-Osorno; Begoña García; Elizabeth O'Gorman; Shafik Oubihi; Jeremy C. Simpson; Iñigo Lasa; Tadhg Ó Cróinín; Margarita Trobos (Biofilm)
Biodegradable polymeric coatings are being explored as a preventive strategy for orthopaedic device-related infection. In this study, titanium surfaces (Ti) were coated with poly-D,L-lactide (PDLLA, (P)), polyethylene-glycol poly-D,L-lactide (PEGylated-PDLLA, (PP20)), or multi-layered PEGylated-PDLLA (M), with or without 1 % silver sulfadiazine. The aim was to evaluate their cytocompatibility, resistance to Staphylococcus aureus biofilm formation, and their potential to enhance the susceptibility of any biofilm formed to antibiotics. Using automated high-content screening confocal microscopy, biofilm formation of a clinical methicillin-resistant Staphylococcus aureus (MRSA) isolate expressing GFP was quantified, along with isogenic mutants that were unable to form polysaccharidic or proteinaceous biofilm matrices. The results showed that PEGylated-PDLLA coatings exhibited significant antibiofilm properties, with M showing the highest effect. This inhibitory effect was stronger in S. aureus biofilms with a matrix composed of proteins compared to those with an exopolysaccharide (PIA) biofilm matrix. Our data suggest that the antibiofilm effect may have been due to (i) inhibition of the initial attachment through microbial surface components recognising adhesive matrix molecules (MSCRAMMs), since PEG reduces protein surface adsorption via surface hydration layer and steric repulsion; and (ii) mechanical disaggregation and dispersal of microcolonies due to the bioresorbable/degradable nature of the polymers, which undergo hydration and hydrolysis over time. The disruption of biofilm morphology by the PDLLA-PEG co-polymers increased S. aureus susceptibility to antibiotics like rifampicin and fusidic acid. Adding 1 % AgSD provided additional early bactericidal effects on both biofilm and planktonic S. aureus. Additionally, the coatings were cytocompatible with immune cells, indicating their potential to enhance bacterial clearance and reduce bacterial colonisation of titanium-based orthopaedic biomaterials.